Changes in coffee and caffeine intake during the pandemic in women smokers and non-smokers: a future challenge for cardiovascular prevention - Coppi, Francesca; Migaldi, Mario; Stefanelli, Claudio; Farinetti, Alberto; Mattioli, Anna Vittoria (Acta Biomedica Atenei Parmensis, 2023)
Background: The recent pandemic has led to major lifestyle changes, especially in women, changes that will impact cardiovascular risk. The aim of the present observational study was to evaluate changes occurred during pandemic in coffee and caffeine intake in a group of adult women and compare changes in smoking versus non-smoking women. Methods: A web questionnaire was sent through a online survey platform to a group of unselected adult women. The consumption of coffee and caffeine were investigated in 2 groups of women by comparing smokers and non-smokers. Results: A total of 435 adult women (256 non-smokers and 179 smokers) answer to all questions. Smokers increase the number of cigarette/days (mean + 3.4 cig/day). Coffee intake was significantly increase in smokers compared to non-smokers (3.1+1.0 versus 1.5+0.6 cups/day p<0.01). In smokers, self-perception of increase stress was related to increased coffee intake (r = 0.84; p <0.001), increased sugar- rich foods (r=0.81; p<0.001), increased chocolate rich snacks (r=0.72; p<0.01), increased sitting time (r=0.79; p<0.01). Conclusions: These preliminary data must suggest to undertake social campaigns aimed at encouraging a return to a healthy lifestyle that certainly includes a healthy diet but also the suspension of smoking. These observational results need further evaluation with prospective studies in order to quantify the effects of pandemic-induced changes in lifestyle on cardiovascular risk in women.